Tax Behavior Analysis and Avoidance Strategies in the Retail Industry - Yamin Noch, Muhammad; Ridwan Rumasukun, Muhammad (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research investigates tax behavior and avoidance strategies in the retail industry through a qualitative literature review. The study aims to identify patterns of tax behavior, assess compliance levels, examine the impact of regulatory changes, and propose policy recommendations. Employing a qualitative approach, the research systematically analyzes existing literature from various sources, including scholarly articles, books, and reports. Data collection involves a comprehensive search strategy using databases such as Scopus and Web of Science. The sampling strategy is purposive, focusing on literature that provides rich insights into tax behavior in the retail sector. Data analysis utilizes grounded theory approach to identify recurring themes and patterns. The findings reveal a complex landscape of tax management strategies employed by retailers, including transfer pricing, the use of tax havens, and financial statement manipulation. The research highlights the role of organizational structures and governance practices in influencing tax behavior, emphasizing the importance of internal controls, transparency, and corporate social responsibility initiatives. Moreover, the implications of tax behavior extend beyond individual firms, affecting governments, consumers, and investors. The study underscores the need for collaborative efforts between policymakers, regulators, and industry stakeholders to promote transparency, fairness, and accountability in the retail tax landscape.